TAUHID DAN ETIKA LINGKUNGAN: Telaah atas Pemikiran Ibn ‘Arabī - Munji, Ahmad (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2014)
Abstract: Tauá¸¥Ä«d (monotheism) affirms that God has created man most excellent among the creatures with the aim to serve Him. Proof of service must be proved by maintaining the best possible environment as He wills. It will consequences which bring up the ethics that guide humans to interact with their environment. Therefore, the relationship of Tauá¸¥Ä«d and ethics as good and bad links or ethical character that relies heavily on clean and dirty soul and reflect the quality of faith (Ä«mÄn) and Tauá¸¥Ä«d (monotheism) itself. This article aims to elaborate on the relationship of Tauá¸¥Ä«d with mindset, because the mindset is mental activity that requires imagination in many ways and requires a balance; Tauá¸¥Ä«d relationship with the pattern of attitudes; patterns of attitude is the basic concept of a person's behavior; relationship between Tauá¸¥Ä«d and behavioral patterns ('amal). 'Amal is a reflection of a very concrete. From this pattern can be described as follows: Tauá¸¥Ä«d produces ethics, and ethics produces behavior ('amal). The pattern of this relationship in real life can be seen, among other things, how human beings interact with other Godâ€™s creatures (environment). Abstrak: Tauá¸¥Ä«d menegaskan bahwa Tuhan telah menciptakan manusia yang paling baik di antara para makhluk dengan tujuan untuk mengabdi kepada-Nya. Bukti pengabdian harus dibuktikan dengan menjaga lingkungan sebaik-baiknya sebagaimana yang dikehendaki-Nya. Konsekuensi dari ini akan memunculkan etika yang memandu manusia dalam berinteraksi dengan lingkungannya. Sebab, hubungan Tauá¸¥Ä«d dan etika seperti keterkaitan baik dan buruknya akhlak atau etika yang sangat bergantung pada bersih dan kotornya jiwa dan mencerminkan kualitas dari iman dan tauhid itu sendiri. Artikel ini bertujuan mengelaborasi hubungan Tauá¸¥Ä«d dengan pola pikir, karena pola pikir adalah aktivitas jiwa yang memerlukan khayal dalam berbagai hal dan membutuhkan keseimbangan; hubungan Tauá¸¥Ä«d dengan pola sikap; pola sikap adalah konsep dasar dari sebuah perilaku seseorang; hubungan antara Tauá¸¥Ä«d dan pola perilaku (â€˜amal). â€˜Amal merupakan cerminan yang sangat kongkrit. Dari sini pola ini dapat digambarkan sebagai berikut: Tauá¸¥Ä«d menghasilkan etika, dan etika menghasilkan perilaku (â€˜amal). Pola hubungan ini dalam kehidupan riil dapat dilihat, antara lain, bagaimana manusia berinteraksi dengan makhluk-makhluk Tuhan yang lain (lingkungan). Keywords: Tauá¸¥Ä«d, â€˜amal, ethic, Ibn â€˜ArabÄ«, AllÄh, enviromenment.